Modern Slavery in the Context of SDG n. 8 - Case Study : Human Trafficking in Cambodia - Kucharčíková, Anna; Sejkora, Jiří, 1985-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This diploma thesis addresses the phenomenon of modern slavery and one of its fundamental forms - human trafficking, which is a development problem on a global scale in the 21st century. The thesis provides a theoretical and historical background of modern slavery, the current state of the problem in the world, and the main factors of this issue, also in the context of Goal No. 8 of the SDGs initiative created by the UN. In the practical part, the status and the leading factors of human trafficking in the South Asian country of Cambodia, a haven of the issue, are examined. The conclusion of the paper comes with the findings that all the selected factors of human trafficking in Cambodia - social and cultural practices and norms; governmental corruption; poverty; and demand for services of trafficked victims, have strong impacts on trafficking in Cambodia in different contexts.
Vedoucí práce: Jiří Sejkora
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor dipl. práce]; diplomové práce; master's theses